Effect of metal artifact reduction level on the assessment of dental implant positioning by cone-beam computed tomography - Capel, Camila Porto (2024)
Objectives: This study evaluated the effect of metal artifact reduction (MAR) level and tube current on the assessment of dental implant positioning regarding the mandibular canal (MC) through cone-beam computed tomography (CBCT). Materials and methods: Dried mandibles with titanium dental implants placed at (Group 1: 0.5 mm superior to the MC/n=8; Group 2: 0.5 mm inside the MC with perforation of the cortex/n=10) were scanned with CBCT at MAR-off, MAR-medium and MAR-high and two tube currents (4mA and 8mA). Four examiners analyzed the images and scored the contact between the implant and the MC using a 5-point scale. ROC analysis and frequency of scores were calculated. Accuracy was compared with ANOVA two-way and Tukey\'s test and scores with Chi-Square test. Results: Area under ROC curve decreased significantly when MAR was at a high level compared with MAR medium and off. Frequency of score 3 (inconclusive) was highest, and scores 1 and 5 (definitely no contact; and definitely contact of the implant with the MC interior) were lowest, when MAR level was high, regardless of tube current. When MAR was off, there were higher frequencies of scores 1 and 5. Conclusion: Different levels of MAR influenced the assessment of dental implant positioning. High MAR level led to lower diagnostic accuracy compared with MAR medium and off. Clinical relevance: This study showed that CBCT-diagnostic accuracy of dental implants can vary depending on the MAR level, which is important in the clinical decision-making process.